The Role of Tropical Atlantic in ENSO Predictability Barrier - Yingying Zhao; Yishuai Jin; Antonietta Capotondi; Jianping Li; Daoxun Sun (Geophysical Research Letters)
Abstract This paper investigates the impacts of tropical Atlantic on El Niño‐Southern Oscillation (ENSO) predictability through an empirical dynamical model‐ Linear Inverse Model (LIM). By selectively including or excluding the coupling between tropical Atlantic and tropical Pacific in LIM, we find that the tropical Atlantic dynamics significantly improve the Eastern Pacific (EP)‐ENSO prediction and weaken the EP‐ENSO predictability barrier (PB), with the Equatorial Atlantic (EA) mode playing a more important role than the Tropical North Atlantic (TNA) mode. The tropical Atlantic impacts on Central Pacific (CP)‐ENSO predictability and PB are relatively smaller. Consistent with observations, the tropical Atlantic can weaken PB in most CMIP6 models. The evolution of the tropical Atlantic optimum initial structures confirms the important influence of the EA mode on the eastern tropical Pacific. Therefore, the tropical Atlantic dynamics, especially the EA mode, should be appropriately considered to improve the prediction of EP‐ENSO and weaken the EP‐ENSO PB.